Analyzing diffuse scattering with supercomputers. Corrigendum. Issue 2 (1st March 2016) - Michels-Clark, T. M.; Lynch, V. E.; Hoffmann, C. M.; Hauser, J.; Weber, T.; Harrison, R.; Bürgi, H. B.
Abstract : Errors in the paper by Michels‐Clark, Lynch, Hoffmann, Hauser, Weber, Harrison & Bürgi [ J. Appl. Cryst. (2013), 46, 1616–1625 ] are corrected. Abstract : Errors in the paper by Michels‐Clark, Lynch, Hoffmann, Hauser, Weber, Harrison & Bürgi [ J. Appl. Cryst. (2013), 46, 1616–1625 ] are corrected.